Integrating Nursing and Laboratory Practices for Enhanced Patient Care and Diagnostics - Noha Jaman Alharbi; Olyan Ibrahim Al Olayan; Ahmed Mufarah Ali Asiri; Alhassan Darwish Alasiri; Khaled Abdullah Hamed Al Gaymah; Reham Ahmad Ali Fadel; Amal Khalil Alnashri; Arwa Ahmed Mohammed Otayf; Kholod Yassin Hadi Jardi; Alanoud Mansour Alamer; Assma Awadh Shammari; Seham Musalam Aljohany (International Journal of Medical Toxicology and Legal Medicine, 2024)
Such a combination of nursing and laboratory practices can only add value to patient care and diagnostics, adding to collaboration. The nurse and laboratory professional thus work in concert in contributing to patient-centered care: one is the first point of contact, and the other as the supplier of important diagnostic information. This paper reviews the available evidence on the benefits of interdisciplinary collaboration between nursing and laboratory teams regarding gains in improved communication, diagnostic accuracy, and resultant patient outcomes. We describe how good teamwork between the two professions ensures appropriate and efficient clinical decision-making, eliminates errors, and optimizes safety for the patient. It also describes how structured communication protocols, shared decision-making, and continuous learning promote high-quality health care. Laboratory practices will need to be integrated into nursing workflows as the healthcare system evolves to further improve overall efficiency and patient satisfaction.